LANGUAGE DOMINANCE REPRESENTATION IN THE UTTERANCES OF A BILINGUAL CHILD: A CASE STUDY OF AN INDONESIAN–JAPANESE CHILD - Devita, Afni Apriliyanti; Refomia, Meidina (Asosiasi dosen IDEBAHASA KEPRI, 2025)
The aim of the research is to describe how language dominance manifested in the spontaneous speech of a bilingual child. It focused on Ritsuki, a 3.5-year-old girl raised in a Japanese-Indonesian household, whose daily interactions were documented on the Ueno Family Japan YouTube channel. This research used psycholinguistics approach, which emphasized that language development was shaped by meaningful interaction and the frequency of use in real-life settings. Using a qualitative case study method, the research examines the child's natural language use across various everyday contexts. For data collection, three video recordings were selected for analysis based on the presence of verbal interactions between Ritsuki and her parents or peers. Each video was transcribed to capture Ritsuki’s utterances and to identify patterns of language use. The analysis focused on lexical choices and contextual cues that indicated language preference or dominance. The findings revealed that Ritsuki demonstrated Japanese dominance during structured routines, such as greetings and activities with her Japanese-speaking father. Indonesian was more commonly used in informal, relaxed conversations with her Indonesian mother and during peer interactions. Overall, these patterns suggested that Ritsuki’s language dominance was context-dependent, shaped by the speakers she interacted with and the social functions of each language in her environment.